Caribbean Report 23-05-1997 - Orr, Carol (anchor); Ninvalle, Pete (correspondent); Phillips, Daphane (interviewee); Fraser, Tony (correspondent); Kinnaird, Charles (interviewee); Smith, Clifford (correspondent); Skerritt, Eugene (interviewee); Goffe, Leslie (correspondent) (The British Broadcasting Corporation, 1997)
Voters have been turning out in large numbers today for St Lucia’s general election inspite of intermittent rain. Prime Minister Vaughn Lewis is seeking re-election alongside an unprecedented forty candidates including seven independents. Next, in Trinidad and Tobago the Ministry of Culture has been accused of discrimination against Indian cultural activity. The Minister, however, has denied such allegations. Next, Trinidad and Tobago has asked Guyana to waive its promised import of twenty-four thousand tons of rice sparking a possibility of a renewed trade row under a Caricom agreement signed by regional states. Next, the European Commission is considering again its tactics for when and how to launch its appeal at the World Trade Organisation against a panel ruling in favour of US complaints against the EU regime. Next, tens of millions of dollars leave the United States each year headed for the Caribbean via a money transfer company like Western Union but sending money home is going to become more difficult in the future because of new US government restrictions designed at clamping down on drug money launderers. Next, the Supreme Court in Florida has suspended executions by the electric chair until September to consider whether its use violates inmate’s rights. Its ruling have provided breathing space for Trinidad born death row inmate Krishna Maharaj whose legal team is seeking British state funds for is appeal. Next, Radio Antilles suspends its operations in a week’s time. Staff at the Montserrat based station have been able to keep broadcasting going despite two years of life in the shadow of an active volcano.
1. Headlines (00:00-00:28)
2. Just minutes left before the polls close in St Lucia. Pete Ninvalle reports (00:29-02:52)
3. Cries of discrimination against Indian cultural activies in Trinidad and Tobago. Cullture Minister, Daphane Phillips is interviewed. Tony Fraser reports (02:53-05:03)
4. A possible trade row erupts between Trinidad and Tobago and Guyana over rice. Head of Guyana Rice Division, Charles Kinnaird is interviewed (05:04-07:20)
Keywords: Elections -- St. Lucia.; Trinidad and Tobago -- Ministry of Culture.; Indian cultural activities -- Trinidad and Tobago.; Rice -- Trinidad and Tobago.; Rice -- Guyana.; World Trade Organisation.; European Commission.; Money laundering -- Caribbean Area.; Maharaj, Krishna.; Electric chair -- Florida.; Radio Antilles -- Montserrat.